Heritage and social events as facilitators of relationship quality in wine sector - Cunha, N.; Loureiro, S. M. C. (Proceedings of the International conference on Tourism and Ageing, 2016)
This study aims to explore how distributors and wine producers describe the organizational social capabilities they develop; as a facilitating facet of Relationship Quality (RQ). A total of eleven relationships are analysed based on 44 in-depth interviews. Findings reveals that Organisational Social Capabilities is a new RQ construct related with the organisational structure, the social behaviour and the history of the company.